Knowledge of pediatric nursing professionals about infiltration and extravasation in newborns and children - Erika Anny Costa Cerqueira; Isaiane Santos Bittencourt; Mariana de Oliveira Lima Caldas; Bianka Sousa Martins Silva; Bruna Figueiredo Manzo; Patrícia Kuerten Rocha; Luciano Marques dos Santos (Rev Rene)
Objective: describe the knowledge of nursing professionals regarding infiltration and extravasation in children using peripheral intravenous catheters. Methods: cross-sectional study carried out with 68 professionals from the nursing team of a pediatric hospital. Data collection took place using a structured questionnaire and we used descriptive statistics to analyze the information acquired. Results: regarding the concept, signs/symptoms, and management of complications, the rate of correct answers was considered low. Regarding risk factors, correct answer rates were medium or high. When it comes to classification, there was a low rate of right responses in the 1st and 3rd degrees of infiltration and in regard to the mechanisms that lead to both types of complication. Conclusion: the rate of correct answers regarding infilgration and extravasation was considered low for most questions. Contributions to the practice: the study may show how necessary it is for pediatric hospitals to plan institutional policies that enable the nursing team to provide the best intravenous therapy practices in order to help improve the quality of the assistance provided to newborns and children.